Toxoplasma Infection Induces Sustained Up-Regulation of Complement Factor B and C5a Receptor in the Mouse Brain via Microglial Activation: Implication for the Alternative Complement Pathway Activation and Anaphylatoxin Signaling in Cerebral Toxoplasmosis - Shinjyo, Noriko; Hikosaka, Kenji; Kido, Yasutoshi; Yoshida, Hiroki; Norose, Kazumi (Frontiers in Immunology, 2021)
Toxoplasma gondii is a neurotropic protozoan parasite, which is linked to neurological manifestations in immunocompromised individuals as well as severe neurodevelopmental sequelae in congenital toxoplasmosis. While the complement system is the first line of host defense that plays a significant role in the prevention of parasite dissemination, Toxoplasma artfully evades complement-mediated clearance via recruiting complement regulatory proteins to their surface. On the other hand, the details of Toxoplasma and the complement system interaction in the brain parenchyma remain elusive. In this study, infection-induced changes in the mRNA levels of complement components were analyzed by quantitative PCR using a murine Toxoplasma infection model in vivo and primary glial cells in vitro. In addition to the core components C3 and C1q, anaphylatoxin C3a and C5a receptors (C3aR and C5aR1), as well as alternative complement pathway components properdin (CFP) and factor B (CFB), were significantly upregulated two weeks after inoculation. Two months post-infection, CFB, C3, C3aR, and C5aR1 expression remained higher than in controls, while CFP upregulation was transient. Furthermore, Toxoplasma infection induced significant increase in CFP, CFB, C3 and C5aR1 in mixed glial culture, which was abrogated when microglial activation was inhibited by pre-treatment with minocycline. This study sheds new light on the roles for the complement system in the brain parenchyma during Toxoplasma infection, which may lead to the development of novel therapeutic approaches to Toxoplasma infection-induced neurological disorders.